KENDALA PELAKSANAAN PROGRAM KOPERASI UNIT DESA PADA MASYARAKAT DI JORONG SUNGAI TANANG KECAMATAN SUNGAI AUR KABUPATEN PASAMAN BARAT - Chandra, Dedi; Oktavia, Dian Anggraini; Fitlayeni, Rinel (Pendidikan Sosiologi, 2014)
Dedi Chandra (09070158) "Constraints Village Unit Cooperative Program Implementation In Public At River Jorong Tanang Aur River District West Pasaman, Education Program High School Sociology Teacher Training and Education (STKIP) PGRI West Sumatra, Padang 2014.This study in the wake of the 7 village cooperatives contained in Aur River District there are several Village Unit Cooperatives (KUD) were not successfully run the program. One of them in Jorong Tanang River. The problems of this research are: 1) What program KUD in Jorong Tanang River, 2) What constraints Village Unit Cooperative Program, 3) what is the solution adopted in Jorong KUD Tanang River.The theory used in this study are George Homans with exchange theory, whereas qualitative research methods with descriptive type, informant selection techniques with a number of informants 21 people. Data collected through observation and interviews, while data analysis is done continuously and interactive at every stage of the research until the research phase is completed.The results of this study explain that (1) the Village Unit Cooperatives (KUD) have programs that run as, a) program improve rural economic cooperatives, b) program KUD independent businesses. (2) Constraints faced by cooperatives in running the program are a) constraints with the company, b) the constraints of society. (3) Solutions in the travel KUD with the company in the form of, a) consultation with the community, while a, b) education and socialization, c) provide assistance to outstanding students, and d) provide capital assistance to people who are creative.